Bistable Smart Window Based on Ionic Liquid Doped Cholesteric Liquid Crystal - Zhaojue Lan; Yong Li; Haitao Dai; Dan Luo (IEEE Photonics Journal)
We develop a bistable smart window based on mixture of negative dielectric nematic liquid crystal, chiral dopant, and chiral ionic liquid (CIL). The developed smart window is driven by dual-frequency modulation, where the transparent state is turned on under an electric field with high frequency (4 kHz), and the scattering state is switched on by an electric field with low frequency (20 Hz). The dual-frequency characteristics of the proposed smart window have been extensively investigated. This smart window has intrinsic features including dual-frequency modulation, simple fabrication process, and excellent stability. This smart window is capable of practical use in modern life as a building wall, sunroof, and curtain-free window.